Meta-Analysis the Effect of Electronic Health Record Utilization on Mortality and Readmission - Syahbaniar, Desi; Tamtomo, Didik Gunawan; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: The development of technology shows a very rapid development, especially in the health sector. One example of the use of technology in the health sector is the electronic health record. Electronic health records provide several benefits, one of which can reduce mortality and readmission rates in patients. The purpose of this study was to estimate the effect of electronic health records on mortality and readmission rates by metaanalysis.Subjects and Method: This was a metaanalysis study using PRISMA flowchart guidelines. The article search process was carried out between 20112022 using databases from PubMed, Google Scholar, ProQuest, Science Direct and Scopus. The PICO formula used is P = patients with asthma. I= using internetbased selfmanagement. C= without using internetbased selfmanagement. O= asthma control. Article searches were performed using the keywords “mhealth” OR “mobile health” OR “telemedicine” AND “self management” AND “asthma control” OR “asthma treatment” AND “asthma control”. The inclusion criteria were full paper articles with randomized controlled trial study design, articles using English, the intervention provided was the application of internetbased selfmanagement, and the outcome was asthma control. Based on the database, there were 9 articles that met the inclusion criteria. The analysis was carried out using Revman 5.3 software.Results: A total of 13 articles spread across 2 continents, namely Asia (Taiwan, Singapore, and South Korea) and North America (South America). Articles reviewed in the metaanalysis showed that electronic health records had an effect on reducing mortality by 0.74 times compared to those without using electronic health records (aOR= 0.74; 95% CI= 0.64 to 0.86; p<0.001). In addition, it was also found that electronic health records had an effect on reducing readmission by 0.77 times compared to without using electronic health records (aOR= 0.77; CI 95%= 0.62 to 0.95; p= 0.010)Conclusion: The application of electronic health records has an effect on reducing mortality and readmission rates.Keywords: Electronic health record, mortalitas, readmissionCorrespondence: Desi Syahbaniar. Masters Program in Public Health, universitas Sebelas Maret. Jalan Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: desiniar15@gmail.com. Mobile: +6287708465646Journal of Health Policy and Management (20220, 07(02): 103-111https://doi.org/10.26911/thejhpm.2022.07.02.02